Cat coexistence in central Sumatra: ecological characteristics, spatial and temporal overlap, and implications for management. (4th February 2015) - Sunarto, S.; Kelly, M. J.; Parakkasi, K.; Hutajulu, M. B.
Abstract At least six species of wild cats live in Sumatra. Many are globally threatened and yet their ecology is poorly understood. We investigated ecological characteristics and spatial and temporal overlap among cats in central Sumatra using data from systematic and opportunistic camera trapping in five major forest blocks. We developed occupancy models assessing probability of site use by each cat based on (1) photo‐trap rates of other species at the same locations and (2) landscape‐level factors extracted from geographic information systems. We also used two‐species co‐occurrence models to assess spatial overlap and used kernel density estimates on circular data to assess temporal overlap between species pairs. We photographed five cat species: Sumatran tigers, Sunda clouded leopards, Asiatic golden cats, marbled cats and leopard cats. Four cats were present in all sampling blocks and one sampling block had all five cats. Spatially, cat distributions varied among forest types, within the sampling blocks and across elevation. We placed camera traps at elevations ranging from 6 to 460 m above sea level. The five cats used statistically different elevations, with golden cats found at highest elevation. Site use by tigers and leopard cats negatively covaried with distance to protected areas. Clouded leopard presence covaried positively with altitude. Leopard cat presence covaried with the photo‐trap rate of tigers, whereas the presence of tigers covaried with the photo‐trap rate of non‐cat carnivores. We found little evidence of spatial avoidance among cats at camera sites. Temporally, species more similar in size, or with similar‐sized prey, had lower overlap, suggesting temporal avoidance. We identified six mechanisms promoting coexistence of central Sumatra cats. Knowledge of interspecific interactions may improve the effectiveness of management aimed at conserving the increasingly threatened wild cat community.